Exploring the intersections between novel psychoactive substances (NPS) and other substance use in a police custody suite setting in the north east of England. (4th July 2018) - Addison, Michelle; Stockdale, Kelly; McGovern, Ruth; McGovern, William; McKinnon, Iain; Crowe, Lisa; Hogan, Lisa; Kaner, Eileen
Abstract: Aims: Novel psychoactive substances (NPS), a range of plant-based/synthetic substances that mimic effects of other illicit substances (e.g. cannabis), are now illegal in the United Kingdom (May 2016) to produce/supply. Negative behavioural consequences of NPS use mean that users frequently transgress the law are arrested and detained in police custody suites. Evidence shows a link between traditional substance use and offending behaviour, with significant police time spent on alcohol-related incidents. We explore the intersections between NPS and other substances with police staff and users in custody; specifically the similarities and differences in treatment, management and policing of these substances. Methods: A qualitative study using semistructured interviews and thematic analysis. We recruited 15 police staff (4 women/11 men) and 25 NPS users (9 women/16 men). Results: Police staff perceived NPS users to be extremely volatile in custody and reported feeling less knowledgeable about how to manage and respond to their needs compared to other substance users (e.g. alcohol, heroin). Users rarely took NPS in isolation and often compared them to other illicit substances, balancing effects versus costs. Conclusion: NPS use has a striking effect on custody work, primarily because of unpredictable user behaviour, adding further pressure to already overstretched police staff.